Endotelina-1 y -3 : efectos moduladores sobre el transportador neuronal de noradrenalina en el hipotálamo de rata. Receptores y vías intracelulares involucradas - Hope, Sandra Ingrid (2017)
In this thesis, we show that endothelin-1 and -3 (ET-1 and ET-3) behave as neuropeptides regulating the activity of the norepinephrine transporter (NET) in the anterior and posterior\nhypothalamus of normotensive rats. The regulation is complex and involves different ET receptor\nsubtypes, including the so called non-conventional or atypical receptors as well as multiple\nsignaling pathways.\nIn the anterior hypothalamus ET-1 reduces neuronal norepinephrine (NE) uptake by\ndecreasing the number of functional transporters without altering its affinity. The inhibitory effect\nof ET-1 is mediated by ETB receptors and involves different signaling pathways including NOS, PKA\nand PKC. These pathways induce the phosphorylation at serine a tyrosine sites which favor NET\ninteraction with syntaxin A1 leading to NET internalization and thereby decreasing the number of\nbinding site at the membrane surface of nerve terminals. Nevertheless, in the same hypothalamic\nregion, ET-3 increases neuronal NE uptake and thus NET activity by increasing the number of\ntransporters available at the neuronal membrane. This occurs as the result of NET mobilization\nfrom intracellular compartments to the membrane surface. ET-3 exerts its effect through the\nactivation of an atypical or non-conventional ET receptor which is coupled to a G protein. The\nactivation of atypical ET receptor / G protein involves different intracellular calcium-dependent\nmechanisms.\nIn the posterior hypothalamus both endothelins decrease NE uptake by reducing NET\nactivity as the result of diminished binging sites at the neuronal membrane. This is achieved\nbecause both endothelins favor NET internalization to intracellular compartments. ET-1 response\nis mediated by ETB receptors whereas that of ET-3 by the activation of an atypical or nonconventional\nET receptor coupled to a G protein. Regardless which receptor is activated, both\nendothelins activate the same intracellular pathways including neuronal NOS, PKA and PKC\nleading to the same response as that of ET-1 in the anterior hypothalamus.\nPresent findings together with previous studies from our laboratory strongly support that\nboth ET-1 and ET-3 behave as neuromodulators of noradrenergic transmission in the in the\nanterior and posterior hypothalamus of normotensive rats through the regulation of three major\nsteps: NET activity (as shown in the present thesis), neuronal NE release and tyrosine hydroxylase\nactivity and expression.\nIn the light of these results we propose that the regulation of cardiovascular physiology\ninduced by brain ETs is mediated by the decreased sympathoinhibition of the anterior\nhypothalamus and the increased sympathoexcitation of the anterior hypothalamus. Thus, our\nfindings may explain the net increase in the central sympathetic activity mediated by ETs\ndescribed by several authors.